2012
DOI: 10.1111/j.1469-8749.2012.04302.x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinimetrics of measures of oropharyngeal dysphagia for preschool children with cerebral palsy and neurodevelopmental disabilities: a systematic review

Abstract: Aim  The aim of this study was to determine the psychometric properties and clinical utility of objective measures of oropharyngeal dysphagia (OPD) in children with cerebral palsy or neurodevelopmental disabilities aged 12 months to 5 years. Method  Five electronic databases were searched to identify measures of OPD. The Consensus‐based Standards for the Selection of Measurement Instruments (COSMIN) Checklist was used to assess psychometric properties and a Modified CanChild Outcome Rating Form was used for cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 46 publications
1
49
0
6
Order By: Relevance
“…Existem escalas para a avaliação da disfagia, como a Dysphagia Severity Scale, que são usadas para indivíduos com deficiência mental ou física em geral, mas não há no Brasil uma escala validada direcionada para avaliação das crianças com PC 36,45 .…”
Section: Disfagiaunclassified
“…Existem escalas para a avaliação da disfagia, como a Dysphagia Severity Scale, que são usadas para indivíduos com deficiência mental ou física em geral, mas não há no Brasil uma escala validada direcionada para avaliação das crianças com PC 36,45 .…”
Section: Disfagiaunclassified
“…21 The aim of the current review was to examine the evidence for the validity and reliability of descriptive ordinal scales used to classify the eating and drinking ability of individuals with CP. These scales could then potentially be adopted in clinical and populationbased research.…”
mentioning
confidence: 99%
“…5,15 Although valid and reliable systems are available to classify movement, 16,17 manual, 18 and communication ability 19 in CP, there is inconsistent use of the measures of eating, drinking, and feeding difficulties. 3,20,21 A survey of international CP surveillance registers revealed that, in 2009, 13 out of 21 active CP registries collected eating and drinking data using 11 different measures. 22 The use of a consistent indicator of eating and drinking ability would enable more rigorous investigation of the prevalence of feeding disorders, and of associations between the severity of eating and drinking limitations and other health indicators such as growth, respiratory health, and gastrostomy use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…-Brief Assessment of Motor Function; -Oral Motor Deglutition Scale; -Behavioral Assessment Scale of Oral Functions in Feeding; -Dysphagia Disorders Survey (DDS); -Feeding Behaviour Scale; -Functional Feeding Assessment; -Gisel Video Assessment; -Oral Motor Assessment Scale; -Pre-Speech Assessment Scale (PSAS); -Schedule for Oral Motor Assessment (SOMA) [18]. Spośród nich DDS, SOMA i PSAS uznano za narzędzia o najlepszych właściwościach psychometrycznych i zarekomendowano je do stosowania u dzieci z zaburzeniami neurorozwojowymi [19].…”
Section: Metody Diagnostyczne Stosowane W Ocenie Zaburzeń Karmieniaunclassified